The Effects of Age at Weaning and Length of Lipid Supplementation on Growth, Metabolites, and Marbling of Young Steers - Tipton, Jessie E. (2020)
The objective of this study was to determine how weaning age, days on supplements, and lipid supplementation affected the growth and marbling deposition of steers. Steers from a single sire were early weaned (n = 24) at 150 ± 11 days of age or traditionally weaned (n = 24) at 210 ± 11 days of age. Steers were assigned to control (n = 12/weaning group) or an isocaloric, isonitrogenous rumen by-pass lipid (RBL, n = 12/weaning group) for either 45 (n = 6/treatment) or 90 (n=6/treatment) days then harvested. Steer body weight (BW) was recorded on days −14 and −7, then BW and blood samples were collected on days 0, 22, 45, 66, and 90. The right rib section of each animal was collected for proximate analysis. Longissimus dorsi from RBL steers had increased lipids compared with control steers (3.6 ± 0.2 vs. 2.4 ± 0.2% on a wet basis; p < 0.0001). Steers fed for 90 days had greater (p = 0.02) concentrations of Longissimus dorsi lipid (3.3 ± 0.2%) than those fed for 45 days (2.7 ± 0.2%). There was a weaning age by treatment by days on feed interaction for intramuscular adipocyte diameter (p = 0.02) in which early weaned RBL fed for 90 days steers had an increased adipocyte diameter compared to the early weaned control fed for 90 and early weaned fed for 45 days steers with all other treatment groups as intermediates. Supplementation of RBL increased concentrations of C18:2, C20:4, and total fatty acids on days 45 and 90 (p ≤ 0.05). Data show that RBL supplementation increased the marbling content of the Longissimus dorsi. Furthermore, a longer period of supplementation resulted in increased adipose diameter.